Design, Synthesis, and Antimicrobial Activities of 1,2,3-Triazole Glycoside Clickamers - Tamer El Malah; Hany F. Nour; Amira A. E. Satti; Bahaa A. Hemdan; Wael A. El-Sayed (Molecules, 2020)
Bacterial resistance remains a significant threat and a leading cause of death worldwide, despite massive attempts to control infections. In an effort to develop biologically active antibacterial and antifungal agents, six novel aryl-substituted-1,2,3-triazoles linked to carbohydrate units were synthesized through the Cu(I)-catalyzed azide-alkyne cycloaddition CuAAC of substituted-arylazides with a selection of alkyne-functionalized sugars. The chemical structures of the new derivatives were verified using different spectroscopic techniques. The novel clicked 1,2,3-triazoles were evaluated for in vitro antibacterial activity against Gram-positive Staphylococcus aureus and Gram-negative Pseudomonas aeruginosa, and the obtained results were compared with the activity of the reference antibiotic “Ampicillin”. Likewise, in vitro antifungal activity of the new 1,2,3-triazoles was investigated against Candida albicans and Aspergillus niger using “Nystatin” as a reference drug. The results of the biological evaluation pointed out that Staphylococcus aureus was more susceptible to all of the tested compounds than other examined microbes. In addition, some tested compounds exhibited promising antifungal activity.